Increased in vitro fitness of multi‐ and extensively drug‐resistant F15/LAM4/KZN strains of Mycobacterium tuberculosis. (18th November 2013) - Naidoo, C. C.; Pillay, M.; Raoult, D.
Abstract The role of fitness in transmission of drug‐resistant strains has been explored in previous studies; but has not been established for F15/LAM4/KZN strains, which were responsible for the extensively drug‐resistant tuberculosis (XDR‐TB) outbreak in Tugela Ferry, South Africa. The biological fitness of 15 clinical strains representing the F15/LAM4/KZN, Beijing, F11 and F28 families was determined by growth, viability and competition assays and correlated with DNA sequencing of eight genes associated with drug resistance and putative compensatory mechanisms. Similar growth rates were observed among susceptible, multidrug‐resistant (MDR) and XDR strains of the KZN and F28 genotypes. In contrast, Beijing and F11 MDR strains demonstrated significantly reduced fitness. Resistant strains exhibited heterogeneous fitness profiles in competition with different susceptible strains, suggesting strain dependence. In addition, co‐culture growth rates were consistently higher than independent growth rates in 13/14 competition pairs. All 14 drug‐resistant strains retained viability, at a low CFU/mL, when paired with susceptible strains. The persistence of such resistant strains could consequently support the acquisition of additional drug‐resistance‐conferring mutations and/or the evolution of compensatory mechanisms. Frequently occurring mutations were detected in KZN and F28 resistant strains whereas, the Beijing MDR strain harboured a less common katG mutation and the F11 MDR strain had no katG mutation. Contrary to drug‐resistant Beijing and F11 strains, the successful transmission of KZN strains, particularly during the outbreak, may be attributed to the presence of drug‐resistance‐conferring mutations associated with little or no associated fitness costs. Amplified growth in co‐culture may be suggestive of in vivo trans‐complementation.